Progresso como emancipação da humanidade na filosofia da historia de Kant - Silva, Luciano da (2013)
The following research refers to an interpretation of Kant s texts about history, and politics as a philosophy of the humanity emancipation. This paper proposes, thus, to establish an intersection point between philosophy of history and political philosophy of Kant. The thesis to be defended is: The man is part of nature, as so many other beings, but their choices are free actions, because they are made from an uncaused principle of freedom. In this sense, the humanity emancipation is a responsibility of each man, as a being is not only belonging to the nature but also culture. The hypothesis is: breaking with the state of rudeness reveals to man the meaning of his life, which is, to become free. This direction is given by culture, which refers to a constant process that apart, in an increasingly way, man from rough state. This process can be called moral progress of humanity, understanding morality by the progress made by mankind in every way, so enabling the improvement increasing human sociability. To develop this hypothesis, the research was divided into three parts: a) the first part corresponds to the first chapter, in which is developed the rational base of human action from the Kantian solution to the problem of freedom in the Third Antinomy of Pure Reason and moral reasoning through the categorical imperative. This foundation is necessary, because it establishes a conformation between the laws of nature and man s free act. From this, it is possible to think of others, such as the state of nature and the civil state, the intractability, which is result from constitution of human nature, with sociability, which is result of overcoming of the state of nature, b) The second part is formed by chapters two and three, which is presented the escape of the man from state of rudeness, entry in the moral world, the construction and development of culture and the possibility of achieving a cosmopolitan civil society that guarantees the human condition of universal citizenship, c) the third part refers to the fourth and final chapter, in which is presented an update of Kantian cosmopolitanism to the present days. This update is realized from a reading of Habermas and Bobbio cosmopolitanisms, who, when making a critique of Kantian philosophy, end up doing an update of this thought. Through this structure, we find that the initial hypothesis is plausible and through it the thesis holds itself. Hence, Kant 's texts about the history and politics can be read as a philosophy of human emancipation according as which man recognizes himself as a being who is part of nature, but his life is the result of your choices. The political and moral progress of humanity is thus for Kant, a real possibility, because it has a sense of a categorical imperative for all mankind.